ANALISIS PEMBERIAN KREDIT MIKRO TERHADAP PENINGKATAN NASABAH STUDI PADA PT. BANK SULUTGO CABANG MANADO - REGAR, RIFKA; AREROS, WILLIAM A.; ROGAHANG, JOULA J. (Sam Ratulangi University, 2016)
Abstract. The purpose of this study was to determine the effect of micro-credit to the increase in customers of PT Bank Sulutgo in Manado. The sample in this study were 60 customers as respondents. The data in this study using statistical parametric approach correlation analysis. Results indicate micro credit effect on the increase in customers. Therefore, PT Bank Sulutgo leaders must pay attention to micro businesses in order to increase the number of clients continues to contribute to the development of micro-enterprises in the city of Manado. Keywords: Micro credit, Improved Customer